Association between Body Mass Index and Serum Uric Acid: mediation analysis involving liver enzymes indicators - Feidan Deng; Qingfeng Wang; Xinyue Wen; Xinyu Xu; Lianxu Jia; Huifang He; Xining Wang; Yanjun Xie; Hongqiu Li; Lichun Qiao; Jing Han (BMC, 2024)
Abstract Background Numerous studies have indicated a growing prevalence of hyperuricemia. Elevated levels of serum uric acid (SUA) have been established as influential factors in conditions such as obesity, metabolic syndrome, diabetes mellitus, gout, and cardiovascular disease. Overweight and obesity are closely related to an increase in SUA. Our objective is to demonstrate the mediating role of liver enzyme in the correlation between body mass index (BMI) and SUA. Methods A total of 5925 adults aged 18 to 65 were included in this cross-sectional study. Logistic regression and mediation analysis were used to investigate the relationship between BMI and hyperuricemia as well as liver enzyme levels. Standard methods were used to determine the biochemical indexes, including SUA, liver enzymes, and blood lipids in the collected samples. Results The study revealed that the prevalence of hyperuricemia was 28.0%. Furthermore, the prevalence of overweight and obesity was as high as 48.5%, with 70.7% of this subgroup presenting with hyperuricemia. There was a positive correlation between BMI and hyperuricemia, and elevated levels of liver enzymes (ALT, AST, GGT) were associated with a higher risk of hyperuricemia. The study also observed a positive correlation between BMI and liver enzymes (ALT, AST, GGT). The study findings suggested that ALT, AST, and GGT played significant mediating roles in the relationship between BMI and SUA. Specifically, the unadjusted model revealed that ALT and GGT accounted for 22.12% and 18.13% of the mediation effects, respectively. Conclusions The study found that BMI is associated with hyperuricemia, where liver enzyme abnormalities may have a mediating role. It is suggested that being overweight or obese may affect liver enzyme levels, leading to increased SUA levels. Controlling weight and liver enzyme levels may help prevent and treat hyperuricemia.